Amino acid identity at one position within the alpha1 helix of both the histidine kinase and the response regulator of the WalRK and PhoPR two-component systems plays a crucial role in the specificity of phosphotransfer. - DEVINE, KEVIN (My University, 2010)
Two-component systems usually function as cognate pairs, thereby ensuring an appropriate response to the detected signal. The ability to exclusively phosphorylate a partner protein, often in the presence of many competing homologous substrates, demonstrates a high level of specificity that must derive from the interacting surfaces of the two-component system. Here, we identify positions within the histidine kinases and response regulators of the WalRK and PhoPR two-component systems of Bacillus subtilis that make a major contribution to the specificity of phosphotransfer. Changing the identity of the amino acid at position 11 within the alpha1 helix of WalK and at position 17 within the alpha1 helix of PhoP altered discrimination and allowed phosphotransfer to occur with the non-cognate partner. Changing amino acids at additional positions of the WalK kinase increased phosphotransfer, while changes at additional positions in PhoP only had an effect in the presence of the change at position 17. The importance of amino acid identity at these two positions is supported by the fact that the amino acid combinations of Ile and Ser in WalRK, and Leu and Gly in PhoPR, are very highly conserved among orthologues, while modelling indicates that these amino acid pairs are juxtaposed in the WalRK and PhoPR complexes.
PUBLISHED
Keywords: Genetics